Predictive factors of ictal SPECT findings in paediatric patients with focal cortical dysplasia - Kudr, Martin; Krsek, Pavel; Maton, Bruno; Malone, Stephen; Jahodova, Alena; Jezdik, Petr; Komarek, Vladimir; Miller, Ian; Jayakar, Prasanna; Resnick, Trevor; Duchowny, Michael (Epileptic disorders, 2013)
AIMS: To identify variables that influence the extent of ictal single-photon emission computed tomography (SPECT) findings in paediatric patients with focal cortical dysplasia (FCD). METHODS: We visually evaluated 98 ictal SPECT studies from 67 children treated surgically for intractable epilepsy caused by FCD. SPECT findings were classified as "non-localised", "well-localised", and "extensive" and compared with parameters of injected seizures (seizure type and duration, injection time, and scalp EEG ictal pattern), presence of structural pathology on MRI, type of surgery performed after SPECT study, and histological findings. RESULTS: A shorter injection time and duration of injected seizure was associated with more localised SPECT hyperperfusion. SPECT findings were not significantly influenced by type of injected seizure. Widespread ictal scalp EEG patterns were associated with extensive SPECT findings. Larger zones of hyperperfusion were more common in patients with lesional MRI and patients undergoing multilobar resections. SPECT studies demonstrating good localisation were more common in patients with mild malformations of cortical development. CONCLUSION: Early ictal SPECT radiotracer injection is crucial for successful localisation of the epileptogenic zone. Seizure duration, type of scalp EEG findings, and presence of structural pathology on MRI may influence the extent of ictal SPECT hyperperfusion, which was associated with certain types of epilepsy surgery as well as histopathological findings.
Keywords: Epilepsy; Magnetic Resonance Imaging; jednofotonová emisní výpočetní tomografie; magnetická rezonanční tomografie; epilepsie; Humans; dítě; Predictive Value of Tests; Child; Ictal SPECT; Female; lidé; elektroencefalografie; epilepsy surgery; focal cortical dysplasia; předškolní dítě; ženské pohlaví; Male; prediktivní hodnota testů; Electroencephalography; mužské pohlaví; Tomography, Emission-Computed, Single-Photon; Child, Preschool